Perbandingan Metode Konstruksi Plat Lantai Sistem Double Wire Mesh Dengan Sistem Half Slab - Tedja, Michael; Prisilla, Anastasia; Carolina, Carolina; Wiharyanto, Dimas E. J.; Susiyo, Johnsen (Bina Nusantara University, 2013)
Floor plate is a structure on two-story buildings or more. Like other structures, floor plate also develops over time. Demands a shorter time jobs at a cheaper cost are some reasons for structures development of house construction. Floor plate can be constructed with two different way: conventional which uses double wire meshand modern uses half slab. The purpose of this study is to determine which floor plate construction methods of double wire mesh and half slab is more efficient in terms of cost and time. The study is conducted using survey, comparative analysis and literature study. The results of this study indicate that both methods have advantages and disadvantages. Double wire mesh method takes cheaper construction costs while half slab method takes faster construction time.